2010
DOI: 10.1021/jf1028152
|View full text |Cite
|
Sign up to set email alerts
|

Method Development and Application To Determine Potential Plant Uptake of Antibiotics and Other Drugs in Irrigated Crop Production Systems

Abstract: Studies have shown the detection of emerging contaminants (ECs), of which pharmaceuticals are a subset, in surface waters across the United States. The objective of this study was to develop methods, and apply them, to evaluate the potential for food chain transfer when EC-containing waters are used for crop irrigation. Greenhouse experiments were performed in which select food crops were irrigated with water spiked with three antibiotics. Field experiments, at two different sites, were conducted. Select crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 27 publications
1
52
3
1
Order By: Relevance
“…The former two methods have been shown to effectively extract pharmaceuticals from plant tissues [1,10,17,[38][39][40]. In this study we began with ASE and ULE methods to extract pharmaceuticals from celery tissues using acetonitrile.…”
Section: Comparison Of Extraction Methodsmentioning
confidence: 99%
“…The former two methods have been shown to effectively extract pharmaceuticals from plant tissues [1,10,17,[38][39][40]. In this study we began with ASE and ULE methods to extract pharmaceuticals from celery tissues using acetonitrile.…”
Section: Comparison Of Extraction Methodsmentioning
confidence: 99%
“…However, this cleanup procedure may also remove PPCPs with high or medium hydrophobicity and should only be used when the target compounds are highly hydrophilic, such as polar antibiotics (Dolliver et al, 2007;Jones-Lepp et al, 2010). Due to the wide range of hydrophobicity of PPCPs, solid-phase extraction (SPE) has emerged as the method of choice as a clean-up procedure (Table 1).…”
Section: Extraction and Cleanupmentioning
confidence: 99%
“…For sample cleanup, liquid-liquid extraction (LLE) with hexane was used to remove undesirable hydrophobic compounds, such as chlorophyllic, fatty and waxy materials (Jones-Lepp et al, 2010). However, this cleanup procedure may also remove PPCPs with high or medium hydrophobicity and should only be used when the target compounds are highly hydrophilic, such as polar antibiotics (Dolliver et al, 2007;Jones-Lepp et al, 2010).…”
Section: Extraction and Cleanupmentioning
confidence: 99%
“…Vegetables commonly consumed raw, such as tomatoes (Sabourin et al, 2012), cucumber (Shenker et al, 2011), broccoli (Wu et al, 2012), onion (Kumar et al, 2005) and carrots (Boxall et al, 2006;Jones-Lepp et al, 2010), have been shown to accumulate antimicrobials. Human pathogens can internalize in plants through root or leaf uptake.…”
Section: Introductionmentioning
confidence: 99%